Use of Social Media to Promote Cancer Screening and Early Diagnosis: Scoping Review - Plackett, Ruth; Kaushal, Aradhna; Kassianos, Angelos P.; Cross, Aaron; Lewins, Douglas; Sheringham, Jessica; Waller, Jo; von Wagner, Christian (My University, 2020)
Social media is commonly used in public health interventions to promote cancer screening and early diagnosis, as it can rapidly deliver targeted public health messages to large numbers of people. However, there is currently little understanding of the breadth of social media interventions and evaluations, whether they are effective, and how they might improve outcomes.
Keywords: Social media; Review; Cancer; Campaign; Health promotion; Public health; Early detection of cancer; Cancer screening; Health care disparities